Allergen immunotherapy, routes of administration and cytokine networks: an update. (June 2014) - Cuppari, Caterina; Leonardi, Salvatore; Manti, Sara; Filippelli, Martina; Alterio, Tommaso; Spicuzza, Lucia; Rigoli, Luciana; Arrigo, Teresa; Lougaris, Vassilios; Salpietro, Carmelo
Allergen immunotherapy is a disease-modifying therapy, effective for the treatment of allergic rhinitis, allergic asthma, conjunctivitis or stinging insect allergy. Allergen immunotherapy involves the administration of increasing doses of allergens with the aim of ameliorating the allergic response. Although precise underlying mechanisms of the induction of immune tolerance remain unclear, immunotherapy has been associated with the induction of distinct subsets of Tregs that eventually lead to peripheral tolerance by inducing a deviation from Th2 to Th1 immune responses. This review focuses on the current knowledge of the mechanisms of immunotherapy in relationship to different routes of administration and also provides a unifying view.